TEACHERâS PERCEIVED CHARACTERISTICS AND PREFERENCES OF MOTIVATIONAL STRATEGIES IN THE LANGUAGE CLASSROOM - Winda Hapsari (TEFLIN Journal: A publication on the teaching and learning of English, 2013)
Motivated language teachers play a crucial role in building and developing studentsâ motivation in the classroom. This study aims to investigate teachersâmotivational strategies in relation to their characteristics and preferences in Indonesian context of EFL instruction, which is an area that receives scant attention with regard to empirical research. The empirical data were collected through survey questionnaires and interviews. Twenty-eightactive teachers volunteered to participate in the present study. Findings show that most of these English teachers perceive themselves as enthusiastic facilitators as they explore a variety of ways to motivate students in the classroom. The majority of participants prefer assigning various learning activities or tasks in order to energize a learning environment. By doing so, teachers can draw studentsâ attention and get them engaged in the classroom. The teachers also integrate teaching materials with engaging pedagogical techniquesthat involve student interaction and movement.